Blood feeding behaviour comparison and contribution of Anopheles coluzzii and Anopheles gambiae, two sibling species living in sympatry, to malaria transmission in Alibori and Donga region, northern Benin, West Africa - Martin C. Akogbéto; Albert Sourou Salako; Fortuné Dagnon; Rock Aïkpon; Michelle Kouletio; Arthur Sovi; Michel Sezonlin (Malaria Journal, 2018)
Abstract Background The main goal of this study was to assess the blood feeding behaviour and the contribution Anopheles coluzzii and Anopheles gambiae, 2 sibling species of An. gambiae sensu stricto. present and living in sympatry in 2 regions of northern Benin targeted for indoor residual spraying (IRS). Methods The study was carried out in 6 districts of 2 regions of Benin (Alibori and Donga). Human landing catches (HLC) performed inside and outside of the households and pyrethrum spray captures (PSC) carried out in bedrooms were used to sample vector populations (An. gambiae and An. coluzzii). Collected mosquitoes were analysed to estimate the human biting rate indoors and outdoors, the circumsporozoite antigen positivity, and the anthropophagic index using ELISA methodology. Polymerase chain reaction was used to estimate the frequency of the knockdown resistance (kdr) L1014F and the ace-1 mutations, 2 markers associated respectively with pyrethroids and carbamate/organophosphate insecticide resistance. Results A higher blood feeding rate was observed in An. gambiae compared to An. coluzzii as well as, a non-pronounced outdoor biting behavior in both species. The latter showed similar anthropophagic and sporozoite rates. However the analysis indicates a seasonal difference in the contribution of each species to malaria transmission associated with shifts in resting behaviour. Anopheles coluzzii females accounted for most of the detected infections: 86% in Alibori and 79% in Donga, during the dry season versus 14.4% and 21.2%, respectively for An. gambiae during the same period. This relationship was reversed in Donga during the rainy season (66% for An. gambiae against 34% for An. coluzzii). Results also indicated lower frequencies of kdr L1014F and ace-1 in An. coluzzii versus An. gambiae. Conclusion Despite similarity in some parameters related to malaria transmission in both surveyed species, An. coluzzii is potentially a more important malaria vector because of high density in the region. It is also ...